Exploring Chemical Catalytic Mechanisms for Enhancing Bonding Energy in Direct Silicon Dioxide Wafer Bonding - Aziliz Calvez; Vincent Larrey; Paul Noël; François Rieutord; Frank Fournel (Applied Sciences)
The influence of pH on silicon dioxide direct bonding is studied, unveiling its role in bonding energy enhancement. We show that the deposition of basic salt or molecules consistently increases the silicon dioxide adherence energy. The underlying mechanisms, including silica hydrolysis and catalysis of siloxane bond formation, are explored. The results offer valuable insights into optimized direct bonding processes for microelectronics and related applications.